THE USE OF VIDEOS TO IMPROVE YOUNG LEARNERS' SPEAKING ABILITY :A Quasi Experimental Research in One Public Elementary School in Sukabumi - Atri Nadia Astarina, - (2012)
The researchentitled"The Use of Videos to Improve Young Learners' Speaking Ability" investigates the effectivenessof videos using to improve young learners' speaking ability including its strength and weaknesses. Itemployed a quasi experimental design towards fifth grade students of elementary school in Sukabumi. The data were obtained through pre and post test, field notes and questionnaires. The obtained data are analyzed by t-test computation supported by grand theories of teaching speaking toward young learners employed by Cameron (2001)and Pinter (2006) and the theory of using videos employed by Candlin (1981) and Sherman (2003). The research reveals that the use of videos is likely to be effective inimproving young learners' speaking ability.Furthermore, it attracts students' attention and promotes theirparticipation. Nevertheless, those strengths might be constrained by high speed of talk, uncommon dialect, high cost and good quality of multimedia.Videos instruction organization can equip students' participation and comprehension. In addition, teachers' competence in selecting appropriate videos, organizing teaching activities and operating the media is highly recommended to have this effective method